Cover - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Determination of the Composition of Fly Ash, Bottom Ash and Lime or Cement Mixtures as Road Base Material. Case Study: Road Preservation of Sp. Kereng - Bereng Bengkel – Pilang – Pulang Pisau, Central Kalimantan Mochammad Yusuf Hilman, Noor Endah Mochtar & Soendiarto Excavation Slopes Stability Analysis with Cracked Soil in the Construction of the Serang – Panimbang Toll Road (STA 54+625) Under Maximum Rainfall Condition Wahyu Purnamayoga, Trihanyndio Rendy Satrya, Mahendra Andiek Maulana & Wahyu Supriyo Winurseto Correlation of Initial Soil Density and Maximum Soil Density Under Drying-Wetting Cycles and Their Soil Erodibility Tia Evriana, Trihanyndio Rendy Satrya, Mahendra Andiek Maulana & Wahyu Supriyo Winurseto The Improvement of Existing Slope Reinforcement System and The Design of Alternative Slope Reinforcements Case Study: Lainea-Awunio Road Section Km 98+050 South Konawe Regency, Southeast Sulawesi Province Nadia Kamila, Mohamad Khoiri & Freddy Siagian Slope Stability for Landslide in Road Preservation Working Packages Ende-Wolowaru and Junction-Kelimutu STA 8+425 Frans Andre Sasarari, Yudhi Lastiasih, Herman Wahyudi & Agustinus Junianto